(untitled) (KULT_online, 2013)
Sabrina P. Ramet analyses the history of the "three Yugoslavias": the interwar kingdom (1918–41), socialist Yugoslavia (1945–91), and the Yugoslav state created in 1992, consisting of Serbia and Montenegro. She examines the successes and failures of the state-building process in the three Yugoslavias. Therefore Ramet focuses in particular on the themes of political legitimacy, political development, and nationalism. The basic thesis Ramet pursues is that, in all three Yugoslavias, there was a permanent crisis of legitimacy, rooted in its elites’ failure to resolve the dual challenges of state-building and legitimation.